2021
DOI: 10.37569/dalatuniversity.11.4.973(2021)
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Critical Electric Fields on the Electronic Distribution of Bilayer Armchair Graphene Nanoribbons

Abstract: We employed tight-binding calculations and Green’s function formalism to investigate the effect of applied electric fields on the energy band and electronic properties of bilayer armchair graphene nanoribbons (BL-AGNRs). The results show that the perpendicular electric field has a strong impact on modifying and controlling the bandgap of BL-AGNRs. At the critical values of this electric field, distortions of energy dispersion in subbands and the formation of new electronic excitation channels occur strongly. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In detail, the tendency of inducing and modulating the energy gap in group 3p + 2 of the armchair ribbons and the zigzag ones is similar under the impact of both transverse and perpendicular electric fields [27][28][29]. On the contrary, the semiconducting-to-metal transition is observed for two groups 3p and 3p + 1 of armchair ribbons under the effect of these electric fields [30]. That is to say, for BL-GNRs, the optical spectra for different families of armchair edges could exhibit diverse transformations under the impact of stimuli and need to be investigated.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In detail, the tendency of inducing and modulating the energy gap in group 3p + 2 of the armchair ribbons and the zigzag ones is similar under the impact of both transverse and perpendicular electric fields [27][28][29]. On the contrary, the semiconducting-to-metal transition is observed for two groups 3p and 3p + 1 of armchair ribbons under the effect of these electric fields [30]. That is to say, for BL-GNRs, the optical spectra for different families of armchair edges could exhibit diverse transformations under the impact of stimuli and need to be investigated.…”
Section: Introductionmentioning
confidence: 88%
“…It has been demonstrated that external electric fields can modulate the electronic properties of BL-AGNRs that changes can be visibly observed in the band structure and the DOS of this material [27][28][29][30]. This means that both the gap size and the electron distribution are modulated significantly with electrostatic potentials.…”
Section: Impact Of An External Electric Field On the Optical And Elec...mentioning
confidence: 99%